THE USE OF NURSING INFORMATICS TO IMPROVE HEALTHCARE OUTCOMES - Wafa johar Alanber, Reem Saket Alanezi, Zahraa mohammed Al shehri, Bader Turki Aladhyani, Bayan Saif Albishe, Khulud Abdullah Mobark Aldosari, Mubarak Dawhim Saad AlDosari, Amal Abdulrahman AL-Bishi, Fatimah Mohammed salh Alamri, Naif Matla Fahad Alotaib,; Meshal Mutlag Mohamad Alotibi, Mishari Mutlag Mohammed Al Otaibi -Soltin Hjrf Zeed Alotibi, Naif Matla Fahad Alotaibi, Abdulrahman Mohammed Bin Yabis, Meshari Mohammed Albayyahi, (Chelonian Research Foundation, 2022)
The ongoing focus on providing patient care based on evidence has implications for the necessary abilities in informatics that should be included into all levels of nursing education programs. The objective of this literature study was to assess the current knowledge and understanding of clinical informatics abilities among registered nurses, as well as to identify the most effective instructional programs for nursing students and faculty. Findings indicate that nurse training programs lack consistent adherence to established criteria when it comes to teaching nursing informatics competence. Another literature gap that was highlighted is the lack of research on the informatics training needs of nurse educators. The findings affirm the need for ongoing study to provide precise guidelines on the anticipated clinical informatics skills of graduate nurses and the specific training requirements for faculty to enhance student learning. The complexity of informatics skills needed of registered nurses has significantly expanded during the last decade. The elevated proficiency level suggests the need for clarity on the current requirements for nursing informatics capabilities. In order to adequately equip graduates, nurse educators must possess the necessary expertise to teach the most up-to-date informatics information. The objective of this integrative review research was to assess the current knowledge and understanding of clinical informatics competences among registered nurses, in order to guide the development of effective instructional programs. Keywords: Nurses, clinical informatics, healthcare, outcomes, patient, review article, instructional programs.